Opportunities and challenges for monitoring terrestrial biodiversity in the robotics age - Pringle, Stephen; Dallimer, Martin; Goddard, Mark A; Le Goff, Léni K; Hart, Emma; Langdale, Simon J; Fisher, Jessica C; Abad, Sara-Adela; Ancrenaz, Marc; Angeoletto, Fabio; Auat Cheein, Fernando; Austen, Gail E; et al. (Nature ecology & evolution, 2025)
With biodiversity loss escalating globally, a step change is needed in our capacity to accurately monitor species populations across ecosystems. Robotic and autonomous systems (RAS) offer technological solutions that may substantially advance terrestrial biodiversity monitoring, but this potential is yet to be considered systematically. We used a modified Delphi technique to synthesize knowledge from 98 biodiversity experts and 31 RAS experts, who identified the major methodological barriers that currently hinder monitoring, and explored the opportunities and challenges that RAS offer in overcoming these barriers. Biodiversity experts identified four barrier categories: site access, species and individual identification, data handling and storage, and power and network availability. Robotics experts highlighted technologies that could overcome these barriers and identified the developments needed to facilitate RAS-based autonomous biodiversity monitoring. Some existing RAS could be optimized relatively easily to survey species but would require development to be suitable for monitoring of more 'difficult' taxa and robust enough to work under uncontrolled conditions within ecosystems. Other nascent technologies (for instance, new sensors and biodegradable robots) need accelerated research. Overall, it was felt that RAS could lead to major progress in monitoring of terrestrial biodiversity by supplementing rather than supplanting existing methods. Transdisciplinarity needs to be fostered between biodiversity and RAS experts so that future ideas and technologies can be codeveloped effectively.
Keywords: delfská metoda; Robotics; Environmental Monitoring; Delphi Technique; monitorování životního prostředí; biodiverzita; zachování přírodních zdrojů; Biodiversity; Conservation of Natural Resources; robotika